Single nucleotide polymorphism in the PrP allele (A136, R154, Q171) in Malpura sheep breed - CHOUDHARY, SHARDA; GUPTA, S C; GUPTA, NEELAM (The Indian Journal of Animal Sciences, 2013)
PCR-SSCP method was used to identify polymorphisms in the 136 (A/V), 154 (R/H), and 171 (R/H/Q) codons of the prion protein gene (PrP) in 50 animals of the Malpura sheep breed from its native tract in and around Malpura Tehsil in Tonk District and parts of adjoining Jaipur district. PCR amplicons of approximate size 358 bp were generated for PrP gene exon-3 partial CD’s covering 352 to 700 nucleotide positions. Alanine (A) at codon 136, arginine (R) at codon 154, and arginine (R) or glutamine (Q) at codon 171, responsible for the presence of 2 alleles (ARR and ARQ) and genotype ARQ/ARQ was found in the analyzed population with the 100% frequency. SNP at codon 114, 127, 184 and 189 are HH/RR, GG/GS/SS, NN/NH and QQ/QL/LL with frequencies of 88.89/11.11, 55.56/11.11/33.33, 88.89/11.11 and 66.67/11.11/22.22 respectively. In all flocks, ARQ/ARQ genotype was the dominant haplotype regardless of sheep sex, age and health. However, the generated data will help for the detection of SNP markers related to disease resistance or susceptibility in India.